THE EXPERIMRNTAL RESEARCH ON SINGLE POINT INCREMENTAL FORMING U-SHAPED METAL BELLOWS - HOU XiaoLi; LI Yan; SHI Xun; YANG MingShun; YUAN QiLong (Jixie qiangdu)
The manufacturing requirements and research status of plastic forming pipe fittings in the industrial field are analyzed. The working principle of single point incremental forming metal bellows is introduced. In order to obtain the influence of process parameters on the forming process and forming quality, the finite element model of U-shaped metal bellows of single point incremental forming was established by the finite element analysis software ABAQUS/Explicit. The experimental platform was built and the experimental research was carried out. The T3 red copper was selected as material, through the experiments under different processing parameters, the corrugated forming height is used as the forming quality testing index, and the effect of the interlayer space, spindle speed and axial feed speed on the processing results in the process of single point incremental machining is obtained. The results show that the spindle speed has the greatest impact on the corrugated height of the metal bellows, followed by the interlayer space, and the axial feed speed has no significant influence on the forming quality. The single point incremental forming of metal bellows is of good quality and high precision when the spindle speed is 450 r/min and the interlayer space is 0.25 mm axial feed speed of 0.2 mm/r. The reliability of the optimization results is verified by simulation and experimental results. It provides a reference for the further application of the process.